The continuous strength method for circular hollow sections in torsion. (1st September 2021) - Vipej Devi, Sanasam; Darunkumar Singh, Konjengbam
Highlights: A first report of Continuous Strength Method (CSM) for torsion member is reported. CSM torsion design equations were proposed for circular hollow section member of carbon steel and stainless steel grades. Existing torsion design guidelines were assessed for their applicability to circular hollow section member. Abstract: The continuous strength method employs the deformation capacity of a cross-section and a simple material model for calculation of strength. The method allows exploitation of significant strain hardening in structural design of metallic materials like stainless steel. An initial attempt and first report of continuous strength method for torsion member is presented in this paper, using finite element analysis. Initially, a numerical parametric study was conducted on circular hollow section member with the aim of generating a database for tubular torsion member using validated finite element models. Four different grades of steel were considered for the study i.e., carbon steel (YSt 310), austenitic stainless steel (EN 1.4301), duplex stainless steel (EN 1.4162) and ferritic stainless steel (EN 1.4003). The parametric results were then used to develop CSM torsion design equations. Further, existing torsion design guidelines in EN 1993-1-1 and AISC 360-16 were also assessed. Overall, on average, CSM design equation was found to give improved, consistent and accurate prediction for all four grades of steel considered, in comparison to the existing design guidelines.